1989
DOI: 10.1111/j.1476-5381.1989.tb11992.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of histamine‐stimulated inositol phospholipid hydrolysis by agents which increase cyclic AMP levels in bovine tracheal smooth muscle

Abstract: 1The effect on histamine-stimulated [3H]-inositol phosphate accumulation of a range of agents which increase the accumulation, or mimic the actions, of cyclic AMP has been investigated in bovine tracheal smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 33 publications
7
45
0
Order By: Relevance
“…This augmentation is presumably the result of some indirect action of H,-receptors since there is no direct effect of HI-receptor activation-on cyclic AMP synthesis (Donaldson et al, 1988b). A relationship between raised cyclic AMP levels and modulation of agonist-induced inositol phospholipid hydrolysis has been observed in a number of tissues, including airway smooth muscle (Hall et al, 1989), platelets (Takai et al, 1982;Watson et al, 1984) and gastric mucosal cells (Puurunen et al, 1987). This raises the possibility that the large accumulation of cellular cyclic AMP that occurs in the presence of both histamine and adenosine may mediate one or both of the actions of adenosine (augmentation or inhibition) on inositol phospholipid hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…This augmentation is presumably the result of some indirect action of H,-receptors since there is no direct effect of HI-receptor activation-on cyclic AMP synthesis (Donaldson et al, 1988b). A relationship between raised cyclic AMP levels and modulation of agonist-induced inositol phospholipid hydrolysis has been observed in a number of tissues, including airway smooth muscle (Hall et al, 1989), platelets (Takai et al, 1982;Watson et al, 1984) and gastric mucosal cells (Puurunen et al, 1987). This raises the possibility that the large accumulation of cellular cyclic AMP that occurs in the presence of both histamine and adenosine may mediate one or both of the actions of adenosine (augmentation or inhibition) on inositol phospholipid hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…[Ca2+]i (Suematsu et al, 1984), by inhibiting the formation of inositol 1,4,5-trisphosphate (InsP3: Madison & Brown, 1988;Hall et al, 1989) or by inhibiting the response of the InsP3 receptor (Supattapone et al, 1988). We reported that 8-bromo cyclic GMP, a membrane-permeable cyclic GMP analogue, (Kai et al, 1987), and nitroglycerin (Kobayashi et al, 1985), which elevates cytosolic cyclic GMP, both reduce…”
Section: B)mentioning
confidence: 99%
“…A notable feature of the histamine HI receptor-mediated inositol phosphate response in a number of smooth muscle preparations, such as bovine trachea (Hall & Hill, 1988;Hall et al, 1989) and the hamster vas deferens smooth muscle cell line, DDT1MF-2 , is its inhibition by agents which can increase the intracellular levels of adenosine 3': 5'-cyclic monophosphate (cyclic AMP). In contrast, the inositol phosphate responses to histamine in guinea-pig and mouse cerebral cortical slices are insensitive to regulation by cyclic AMP elevating agents (Alexander et al, 1989;Hollingsworth & Daly, 1985 (Hosli & Hosli, 1984 (Inagaki et al, 1989) and activation of these receptors has been shown to stimulate phosphoinositide hydrolysis (Arbones et al, 1988).…”
Section: Introductionmentioning
confidence: 99%